(untitled) (SketchIN, 2017)
This paper describes the advantages and opportunities of the city of Querétaro to become a smart city, developing products that use renewable energy to achive it. Some tools from Karl Ulrich’s Frontal Process and Bruno Munari’s Proyectual Methodology were used as design methodologies for the development of a solar charging station for mobile devices that allowed the integration of the technology with the needs of the user, demonstrating the importance of design as a catalyst for the development of innovative products for the cities of the future.